Addressing Environmental Design in Interior Architecture Education : Reflections On The Interior Design Studio - Garip, Banu; Garip, Ervin (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2012)
Today, the fluid and multi-layered structure of the environment demands design professions acquire a broader perspective in conjunction with a more expanded, cross-boundary knowledge and skills. This paper mainly concentrates on the structure of interior architectural studies and the significance of environmental design. The study presents a descriptive reading through the experiences in the interior design studio, and in this sense evaluates the outcomes within the educational process. The aim is to discuss the relationship between the interior/exterior or environment/building through the ideas created in the interior design studio. The key points are elucidated through examples of student work from two different interior architecture departments in Istanbul. The reflections upon developing the knowledge of "environmental consciousness" and establishing the dialogue between different scales of environment on student work are examined and discussed in the scope of this paper. Selection and/or peer review under responsibility of Prof. Dr. Ayse Cakir Ilhan.
Keywords: cross-boundary design; interior design education; environmental design; design studio; sınır ötesi tasarım; iç mekan tasarımı eğitimi; çevre tasarımı; tasarım stüdyosu